Juridical Analysis of The Crime of Theft Committed Jointly by Members of The TNI - Gea, Alex Sokhian; Sihotang, Lesson; Sinaga, Jusnizar (Universitas Islam Sultan Agung, 2025)
The criminal act of livestock theft causes material losses and impacts the social and economic lives of farmers. Livestock theft is driven by environmental factors, lack of legal awareness, economic conditions, opportunities, and other social factors. This study aims to analyze the enforcement of the law applicable in handling cases of livestock theft committed by members of the Indonesian National Armed Forces (TNI) and to determine the sanctions imposed on TNI members involved in livestock theft to provide punishment and assess its implications for the image of the TNI. The research method used is a normative legal approach, which involves an in-depth examination of the issue by collecting library data and analyzing it to draw conclusions. The data analysis applied is descriptive analysis to interpret qualitative data, where the researcher uses materials such as legislation, court decisions, journals, and books. The findings of this study reveal that the criminal act of theft committed collectively by TNI members is regulated under Article 363 paragraph (1) 1 in conjunction with Article 55 paragraph (1) of the Indonesian Criminal Code (KUHP) and Article 126 of the Military Penal Code (KUHPM). The Military Court has the authority to try TNI members who commit criminal acts based on Article 9 of Law No. 31 of 1997, taking into account violations of military honor under Article 126 of the Military Penal Code, which relates to its implications for the image of the TNI.